PENYUSUNAN ANGGARAN PENDAPATAN BELANJA DAERAH (APBD) KOTA BUKITTINGGI DITINJAU DARI ASPEK MANAJEMEN DAN MASLAHAH - Kuliman Kuliman; Nisaul Mardiah (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2020)
This research is motivated by the role of the Regional Budget Revenue (APBD) in the welfare of the community. The APBD of the City of Bukitttinggi needs to be criticized as an effort to improve and appropriately suggest the use of the APBD, because if the APBD is well managed then the community will benefit, but if not then the community will not feel the benefits.In general, this study aims to describe the Preparing the Regional Budget for the City of Bukittinggi: An Overview of Management and Maslahah Aspects .This research uses descriptive analysis type of research. The focus of his research is on the preparation of regional revenue and expenditure budget designs in the city of Bukittinggi based on the Bottom Up and Top Dwon approach which will later be associated with management functions namely , Planning, Organizing, Actuating, and Controlling (POAC) and then reviewed with aspects to Maslahahan .Data collection instruments are interviews and observations at the research location and also based on documents and related articles. The data anasilis technique is qualitative. The results of this study indicate that in the Process of Preparing and Utilizing Regional Budget and Revenue (APBD) in the City of Bukittinggi: An Overview of Management Aspects there is a suitability and incompatibility, especially in terms of the time of preparation and the determination that is not timely.Then from the aspect of Maslahah, it was found that there were maslahah both ' Ammah and Khassah .